Identification of a novel ITGαvβ6-binding peptide using protein separation and phage display - Altmann, Annette; Sauter, Max; Rösch, Saskia; Mier, Walter; Warta, Rolf; Debus, Jürgen; Dyckhoff, Gerhard; Herold-Mende, Christel; Haberkorn, Uwe (Clinical cancer research, 2017)
Purpose: Targeted therapies are regarded as promising approaches to increase 5-year survival rate of head and neck squamous cell carcinoma (HNSCC) patients.Experimental design: For the selection of carcinoma-specific peptides membrane proteome of HNO97 tumor cells fractionated by the ProteomeLab PF2D system and corresponding HNO97 cells were deployed for an alternating biopanning using a sunflower trypsin inhibitor1-based phage display (SFTI8Ph) library. Stability, binding properties and affinity of novel candidates were assessed in vitro using radio-HPLC, binding experiments and surface plasmon resonance assay (SPR), respectively. Subsequently, the affinity of the peptide was verified in situ by using peptide histochemistry, in vitro using flow cytometry, and in vivo by positron emissions tomography (PET/CT).Results: We identified a novel ITGαvβ6 binding peptide (SFITGv6) containing the amino acid sequence FRGDLMQL. SFITGv6 provides stability over a period of 24 hours and demonstrates high affinity (KD = 14.8 nmol/L) for ITGαvβ6 In HNO97 cells, a maximal uptake and internalization of up to 37.3% and 37.5%, respectively, was measured. Small-animal PET imaging and biodistribution studies of HNO97 xenografted Balb/c nu/nu mice showed tumor-specific accumulation of 68Ga- and 177Lu-labeled DOTA-SFITGv6, respectively, 30 to 60 minutes after injection. Moreover, peptide histochemistry revealed a strong and homogenous binding of biotin-labeled SFITGv6 to HNSCC tumors and breast- and lung cancer-derived brain metastases. Finally, first PET/CT scans of HNSCC and NSCLC patients displayed SFITGv6 accumulation specifically in tumors, but not in inflammatory lesions.Conclusions: Thus, SFITGv6 represents a novel powerful tracer for imaging and possibly for endoradiotherapy of ITGαvβ6-positive carcinoma. Clin Cancer Res; 23(15); 4170-80. ©2017 AACR.